Pediatric Scurvy: When Contemporary Eating Habits Bring Back the Past - Brambilla, Alice; Pizza, Cristina; Lasagni, Donatella; Lachina, Lucia; Resti, Massimo; Trapani, Sandra (Frontiers in Pediatrics, 2018)
Vitamin C deficiency is anecdotal in developed countries, mainly associated with underling clinical morbidities as autism or neurological impairment. Chronic insufficient dietary supply is responsible for vascular fragility and impaired bone formation, resulting in gingival bleeding, petechial lesions, articular and bone pain or limb swelling. Children may present anorexia, irritability, failure to thrive, limping or refusal to walk. Accordingly, pediatric scurvy is frequently misdiagnosed with osteomyelitis, septic arthritis, bone and soft tissue tumor, leukemia, bleeding disorders, and rheumatologic conditions. We report the case of a 3-years old child developing scurvy as consequence of strict selective diet; extensive and invasive investigations were undertaken before the correct diagnosis was considered. Despite being considered a rare condition, scurvy still exists nowadays, even in children with no apparent risk factors living in wealthy families. The increasing popularity of dietary restriction for children, especially those with allergies, may potentially enhance the occurrence of scurvy in apparently healthy children. Appropriate dietary anamnesis is fundamental in order to highlight potential nutritional deficit and to avoid unnecessary invasive diagnostic procedures. Patients without considerable risk factors may benefit from psychological support in order to investigate possible eating disorders.